Acoustic wave sensors - LEC, R.M. (Archives of Acoustics, 1996)
Acoustic waves excited in a piezoelectric medium provide an attractive technology for realizing a variety of sensor that exhibit high sensitivity, small size and portability, fast responses, ruggedness and robustness, high accuracy, compatibility with integrated circuit (IC) technology, excellent aging characteristics and the capability to measure multiple quantities in one sensor package. Sensors based on this technology can be produced using standard photolithography and hence are inexpensive. In this paper acoustic sensing mechanisms and a wide range of bulk and surface acoustic waves used in the sensor development are described. Applications of acoustic sensors in the chemical, environmental, medical, automotive and aeronautic industries are also given.